Parenting style patterns and their longitudinal impact on mental health in abused and nonabused adolescents - Wassilis Kassis; Aikaterini Vasiou; Dilan Aksoy; Céline Anne Favre; Sibylle Talmon-Gros Artz; Doug Magnusson (Frontiers in Psychiatry)
BackgroundWhile the impact of parenting styles on adolescents’ mental health is well documented, no study has used latent person-oriented methods to analyze the effects of parenting style trajectories, experienced by physically abused and nonabused adolescents from early to middle adolescence, on mental health outcomes.MethodIn this longitudinal study, we used latent transition analysis (LTA) to detect parenting patterns and their trajectories among 1,709 adolescents from 44 high schools in Switzerland across three data waves (2021-2023) by applying a multigroup comparison between physically nonabused and abused adolescents. Using multinomial regression, we tested the effects of the detected parenting patterns on adolescents’ mental health.ResultsAlong with the two known patterns, termed “supportive” and “negative” parenting, two new parenting patterns which we termed “absent” (low levels on all tested parenting styles) and “ambiguous” (middle to high levels on all tested parenting styles) emerged as playing a key role in the perceptions of adolescents with and without parental abuse experience longitudinally. These four patterns developed in diverse ways: Supportive parenting decreased for abused adolescents over time but remained stable for the nonabused adolescents. The absent parenting level was stable over time among abused adolescents when compared to the outcomes experienced by adolescents subjected to the negative parenting pattern. Furthermore, we found a remarkable decline in the number of nonabused adolescents in the absence pattern from Wave 1 to Wave 3. Further, we also found that abused adolescents reported more negative parenting than nonabused adolescents. Additionally, we found that supportive parenting was beneficial for adolescents’ mental health whereas negative, ambiguous, and absent parenting all had detrimental effects.ConclusionsThese findings highlight the beneficial association of supportive parenting and the detrimental effects of negative, ambiguous, and absent parenting. This also suggests that we must consider a more complex approach that involves examining a blend of different parenting styles when analyzing adolescent mental health.